Long wavelength infrared sensor array using VO2 microstructures fabricated on visible GaN LED - Minhyeok Shin; Anh Thi Dieu Nguyen; Taenam Kwon; Jaesung Kim; Miju Park; Nafila Amalia Syahida; Kunook Chung (Scientific Reports)
Abstract The vanadium dioxide (VO2) microstructure arrays were integrated with In x GaN 1–x light-emitting diodes (LEDs) to develop a long-wavelength infrared sensor array. By utilizing GaN-based LEDs as a readout unit, the VO2/LED heterostructure directly converts temperature-induced resistance changes into visible light emission. The VO2 layer exhibits uniform chemical configuration and atomic bonding, leading to consistent metal-to-insulator transition behavior across all pixels. The low-voltage operation was available at 2.5 V, which was readily above the turn-on voltage of the LED. The brightness of the LED and the resistivity changes of the VO2 layer were inversely proportional, where the temperature variations can be gauged optically. Moreover, the VO2/LED heterostructure pixels are individually addressable, which can detect directions and degrees of external heat.